2020
DOI: 10.1038/s41368-019-0070-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of ankylosed primary molars with infraocclusion

Abstract: Primary molar ankylosis with infraocclusion can retard dental arch development and cause dental asymmetry. Despite its widespread prevalence, little is known about its molecular etiology and pathogenesis. To address this, RNA sequencing was used to generate transcriptomes of furcal bone from infraoccluded (n = 7) and non-infraoccluded (n = 9) primary second molars, all without succeeding biscuspids. Of the 18 529 expressed genes, 432 (2.3%) genes were differentially expressed between the two groups (false disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…There is no evident aetiology of infraocclusions in the literature; however, it is possible to identify a specific histological profile. Histologic studies on primary molars in infraocclusion revealed degenerative changes in the pulp, such as fibrosis, calcifications, and areas of reduced cell activity in the periodontal ligament [ 21 , 22 ]. Ankylosis is histologically defined as the fusion of cementum/dentin to the bone in at least one area, resulting in the loss of the periodontal ligament space.…”
Section: Introductionmentioning
confidence: 99%
“…There is no evident aetiology of infraocclusions in the literature; however, it is possible to identify a specific histological profile. Histologic studies on primary molars in infraocclusion revealed degenerative changes in the pulp, such as fibrosis, calcifications, and areas of reduced cell activity in the periodontal ligament [ 21 , 22 ]. Ankylosis is histologically defined as the fusion of cementum/dentin to the bone in at least one area, resulting in the loss of the periodontal ligament space.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated ankylosis to be present in infraoccluded primary molars with missing successors. Although the majority of infraoccluded teeth are non-ankylosed, histological ankylosis can occasionally be found (7) .…”
Section: Introductionmentioning
confidence: 99%